Multi-factor orthogonal optimization and experimental performance study of flow passages in a vertical mixed-flow pump unit - Jiamin Zhang; Zhuangzhuang Sun; Songshan Chen; Ning Lu; Yujing Qiao (PLoS ONE, 2026)
Flow passage optimization is an essential approach for enhancing the efficiency and operational stability of vertical mixed-flow pump units. To address the limitations of the traditional single-factor control variable method—which ignores parameter interaction effects and relies on empirical judgment for scheme screening, leading to low optimization efficiency and insufficient engineering adaptability—this study proposes a multi-factor interactive flow passage optimization methodology that deeply couples orthogonal experimental design with Computational Fluid Dynamics (CFD) simulations. A multi-indicator quantitative evaluation system encompassing “hydraulic loss, velocity uniformity, and weighted average angle” was constructed. Taking a large-scale drainage pumping station as the research object, key parameter combinations were systematically covered through orthogonal experiments. The optimal intake flow passage scheme was screened via CFD simulation, which was verified to have a hydraulic loss of only 0.104 m, an outlet velocity uniformity of 97.06%, and a weighted average angle of 84.82°, approaching the ideal vertical inflow, thereby effectively reducing flow impact losses. The optimal discharge flow passage scheme demonstrated smooth flow patterns without significant flow separation and was fully compatible with the spatial layout of the pumping station. Model test validation showed that under the design head condition of 7.1 m, the pump unit efficiency reached 77.34% with a flow rate of 11.38 m 3 /s. The error between CFD simulation and experimental results was less than 5%, meeting the design requirements. This study provides a scientifically efficient and engineeringly feasible technical pathway for flow passage optimization in similar vertical mixed-flow pump units.